PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ACCELERATED INSTRUCTION DIINTEGRASIKAN DENGAN MEDIA PEMBELAJARAN PAPAN TEMPEL TERHADAP HASIL BELAJAR SISWA SMAN 2 LUWU UTARA - khaerati (Universitas Cokroaminoto Palopo, 2021)
This study aims to determine the effect of the cooperative learning model type accelerated instruction integrated with sticky board learning media on student learning outcomes in class XI IPA SMAN 2 Luwu Utara class movement system material. The type of research was experimental research, using a quasi-experimental method, and the form of the research design was non-equivalent control group design. The instruments used in this study were learning outcomes tests, and learning implementation questionnaires. Sampling was done by purposive sampling technique. The results of learning biology based on descriptive analysis obtained an average posttest score of 88.25 for the experimental class with a very high category, and the posttest results for the control class with an average value of 81.64 with a high category. The results of the inferential analysis using the ANAKOVA test obtained a significant value of 0.003 <0.05, it can be concluded that there is an effect of learning outcomes using the team accelerated instruction cooperative learning model integrated with sticky board learning media.